(untitled) (American Journal of Islam and Society, 1996)
Unlike Christianity, where normative thought is expressed in theological writings, in Islam normative thought is expressed in legal tradition. According to this tradition, the purpose of Islamic society is to submit to God‘s will, which is expressed clearly through revelation: Human beings are to create a just society. As political activity is essential for the creation and maintenance of social justice, all political activity is essentially religious activity in Islam. Thus, the discussion of political activity is highly developed and wide-ranging in Islamic legal texts. In this paper, I focus on discussions of the source of political authority in the ideal Islamic state. Among contempomy commentators on Islam, it has become popular to claim that there is no separation of religion and politics in Islam. This claim, combined with the rejection of secularism by many contemporary Muslim activists, has led some observers to assume that Islam espouses a kind of theocracy. However, this is not the case; the term “nomocracy” is more suitable to describe Islamic political theory. A theocracy is a state governed by God/gods or those who claim to act on divine authority. A nommcy, by contrast, is a state governed by a codified system of laws. The ideal Islamic state is one governed by individuals or bodies bound by Islamic law.’ In this context, classical Islamic legal theory implicitly distinguishes between those empowered to interpret the law (the legislative and judicial branches) and those empowered to make sure the law is being followed (the executive branch). Executive political power-with its coercive authority-ideally would concern itself with safeguarding Islamic law. But because it is subject to abuse, the formulators of Islam’s classical theory of political authority considered it an unreliable repository of religious ...